Development of guidelines for fitness training based on local wisdom of the Malind Tribe to victims of drug abuse - Arifin Ika Nugroho; Hendra Jondry Hiskya; Carolus Wasa; Jori Lahinda (UIR Press, 2021)
Drug abuse is a social problem with a very wide negative impact and in its recovery it needs several solutions. The emphasis of the discussion in this study is the fact in the field that it shows the pattern of implementation of physical and health guidance so far it has only been an unstructured, measurable, and comprehensive implementation. The research is aimed at developing fitness training guidelines and healthy lifestyles based on local wisdom for victims of drug use that are feasible and effective, which will be provided to victims of drug use in the border communities of Indonesia-Papua New Guinea, Merauke Papua. The method used in this research is the Research and Development method, it is chosen as a method for producing certain products and testing the effectiveness of the products to be developed, namely guidelines for fitness training and healthy lifestyles based on local wisdom for drug use victims. The steps of data collection techniques in this research are preliminary study, planning, initial draft, draft trial, small and large scale data, final product, and effectiveness test (Cooper test-12 minutes). The population in this study amounts to 20 people consisting of officers/practitioners in indigenous communities/villages and victims of drug abuse in the Indonesian-Papua New Guinea Border Community, Merauke Papua. The sampling technique in this study uses purposive sampling. The data analysis technique used in this research is quantitative descriptive analysis and descriptive analysis. The results of the study show the feasibility and effectiveness of developing guidelines for fitness training and healthy living patterns based on local wisdom that can be used for drug use victims in the border communities of RI-PNG Merauke Papua.